2015
DOI: 10.1177/1066896915580433
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mixed Adenoneuroendocrine Carcinoma of the Gallbladder in a 55-Year-Old Female Patient

Abstract: Mixed adenoneuroendocrine carcinomas (MANECs) of the biliary tract are rare tumors, and to date only a few cases arising in the gallbladder have been reported. Their histogenesis is a matter of debate, since the biliary tract normally lacks neuroendocrine cells. However, the immunohistochemical identification of nonneoplastic neuroendocrine cells in both biliary adenocarcinomas and intestinal metaplasia has been documented. Here we report a case of a 55-year-old female patient presenting with right upper quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…17,20,24,25 MACROSCOPIC AND MICROSCOPIC FEATURES Macroscopically, biliary MANECs are solid, polypoid, nodular, or papillary tumors with a firm consistency and a homogeneous tan to gray-white cut surface (Figure 1, A). 14,19,21 Focal hemorrhage, necrosis, and mucin-filled cysts can also be evidenced on gross examination. 19,21 Microscopically, biliary MANECs usually have 2 (AC/ SCC-NET) or more histologic components without a Abbreviations: ChT, chemotherapy; ChXrT, chemoradiotherapy.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…17,20,24,25 MACROSCOPIC AND MICROSCOPIC FEATURES Macroscopically, biliary MANECs are solid, polypoid, nodular, or papillary tumors with a firm consistency and a homogeneous tan to gray-white cut surface (Figure 1, A). 14,19,21 Focal hemorrhage, necrosis, and mucin-filled cysts can also be evidenced on gross examination. 19,21 Microscopically, biliary MANECs usually have 2 (AC/ SCC-NET) or more histologic components without a Abbreviations: ChT, chemotherapy; ChXrT, chemoradiotherapy.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…transition zone (collision pattern in Lewin's original classification; Figure 1, B). 2,14,17,27,28 Less frequently, the NET and AC/SCC components are tightly intermingled, without a clear separation (combined pattern). 19,25 A biliary MANEC containing biphenotypic (NE-AC) tumor cells has been reported only once, to the best of our knowledge.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…CDX2, a homeobox gene, is involved in the differentiation and maintenance of enteric epithelium [16] and is known to be a useful immunohistochemical marker of intestinal metaplasia of the gallbladder [17]. Acosta et al reported a case of gallbladder MANEC that was positive for CDX2 in both tumor components and concluded that the finding supported the metaplasia–dysplasia–carcinoma sequence [18]. In the present case which is non-matching as MANEC, the adenocarcinoma component of the primary tumor and the intestinal metaplasia lesions were positive for CDX2 but the neuroendocrine cells were not (Fig.…”
Section: Discussionmentioning
confidence: 99%